Politics and Pigskins: Leader Political Support and Doug Williams’s Termination from Grambling State University - B. Parker Ellen III (Journal of Applied Sports Management, 2016)
Management research long has benefitted from the examination of sport teams and organizations to inform its theories. Similarly, sport management research can benefit from the investigation of business organization research concepts. In the present study, a narrative case study approach is taken to review Doug Williams’s second tenure as Grambling State University’s head football coach. Archival data (i.e., media reports, university communications, and court documents) indicated that Grambling University was an environment ripe for political behavior. Further, the data reveal that Williams’s social capital and political will led to his demonstration of political support for his players, and that this behavior created loyalty and commitment from Williams’s followers (i.e., his players), but simultaneously generated anger and resentment among his superiors (i.e., the university president and athletic director), and resulted in Williams’s termination. Thus, the presently reviewed case indicates politics is a viable area of future exploration for in sport organization research.
Keywords: organizational politics; political behavior; case study